The Institutation of the Foster Family for Mentally Ill Patients in Greece – Views of Patients - Dr., Despina Sikelianou (International Journal of Psychosocial Rehabilitation, 2014)
The aim of this study was to investigate the views of parents on the institution of Foster Families for mentally ill patients in Greece. Specifically, the study concerned the knowledge of parents regarding the concept and the aim of foster care programmes for mentally ill patients, their views on the application of these programmes in Greece and the incentives of candidate foster families for mentally ill patients. The research was implemented in April 2010 and took place in two (2) Prefectures of Greece, the Prefecture of Attica (Pallini) and the Prefecture of Fthiotida (Lamia). The sample consisted of three hundred and twenty two (322) parents, (one hundred and seven (107) men and two hundred and fifteen (215) women), who were members of active Primary and Secondary Education Parent – Guardian Associations in the respective afore- mentioned cities. The research tool used was the questionnaire and the research was quantitative. In accordance with these research results, the majority of parents tend to hold a positive attitude towards the existence and function of this institution. Moreover, the majority of parents believe that Greek society is not ready to accept this institution, mainly because there is lack of support from mental health specialists and Greek society is not sensitized to this institution